STaRT-RWE: structured template for planning and reporting on the implementation of real world evidence studies. (12th January 2021) - Wang, Shirley V; Pinheiro, Simone; Hua, Wei; Arlett, Peter; Uyama, Yoshiaki; Berlin, Jesse A; Bartels, Dorothee B; Kahler, Kristijan H; Bessette, Lily G; Schneeweiss, Sebastian
Abstract : In alignment with the International Council of Harmonization's strategic goals, a public-private consortium has developed a structured template for planning and reporting on the implementation of real world evidence (RWE) studies of the safety and effectiveness of treatments. The template serves as a guiding tool for designing and conducting reproducible RWE studies; set clear expectations for transparent communication of RWE methods; reduce misinterpretation of prose that lacks specificity; allow reviewers to quickly orient and find key information; and facilitate reproducibility, validity assessment, and evidence synthesis. The template is intended for use with studies of the effectiveness and safety of medical products and is compatible with multiple study designs, data sources, reporting guidelines, checklists, and bias assessment tools.